The interdisciplinary theatre of Ping Chong exploring curiosity and otherness on stage - Kurahashi, Yuko 1961- (Jefferson, North Carolina McFarland & Company, Inc., 2020)
This first-ever biography exploring the life of Ping Chong (1946), successful avant-garde artist and Presidential Medal of Freedom recipient, focuses on his valuable contributions to modern theatre. Drawing on primary sources and her own attendance of Chong's productions, the author takes a broad and informative approach to his work as a performer, playwright and director over 48 years.
Includes bibliogrpahical references and idex.
Keywords: Asian American theater -- History and criticism; Experimental theater -- United States -- History and criticism